The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4236/ijg.2012.34079
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical and Geotechnical Investigations of a Landslide in Kekem Area, Western Cameroon

Abstract: Geophysical and geotechnical surveys were conducted in the Western Cameroon (Kekem area) following a landslide on argillaceous material in order to understand the triggering processes and mechanisms of this landslide and to assess the stability of the slope. The geophysical soundings consisting of vertical electrical soundings with the Schlumberger electrode array configuration were carried out to monitor the behaviour of electrical resistivity in the landslide. Geoelectrical data showed a zone of low resistiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Changes in water conditions and slope geometry are the main factors that induce slope instability (Tang et al, 2018) in the presence of discontinuities such as faults, fractures, and beddings which are precursors to landslide (Chalupa et al, 2018). Since, the world is experiencing heavy and extreme rainfall events because of global climate change (Kirschbaum et al, 2020), the continuous precipitation during typhoon increases slope instability around mountains which has led to severe mudflows and landslide events (Baum et al, 2010;Pradhan and Lee, 2010;Epada et al, 2012;Jeong et al, 2014;Chien et al, 2015;Hakro and Harahap, 2015;Baharuddin et al, 2016;Sidle and Bogaard, 2016;Jeong et al, 2017;Kumar and Rathee, 2017;Soto et al, 2017;Tomás et al, 2018;Kirschbaum et al, 2020). A majority of these landslides have caused a considerable loss of lives and properties (Choi and Cheung, 2013;Askarinejad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in water conditions and slope geometry are the main factors that induce slope instability (Tang et al, 2018) in the presence of discontinuities such as faults, fractures, and beddings which are precursors to landslide (Chalupa et al, 2018). Since, the world is experiencing heavy and extreme rainfall events because of global climate change (Kirschbaum et al, 2020), the continuous precipitation during typhoon increases slope instability around mountains which has led to severe mudflows and landslide events (Baum et al, 2010;Pradhan and Lee, 2010;Epada et al, 2012;Jeong et al, 2014;Chien et al, 2015;Hakro and Harahap, 2015;Baharuddin et al, 2016;Sidle and Bogaard, 2016;Jeong et al, 2017;Kumar and Rathee, 2017;Soto et al, 2017;Tomás et al, 2018;Kirschbaum et al, 2020). A majority of these landslides have caused a considerable loss of lives and properties (Choi and Cheung, 2013;Askarinejad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have shown that the increasing or decreasing tendency of soil geomechanical properties can create weaknesses in these soil textures, easing their failure or sliding [ 7 , 69 , 74 ]. In other words, some of these geomechanical properties should be decreasing to make the site more susceptible to landslides.…”
Section: Resultsmentioning
confidence: 99%
“…However, the study of rock and soil characteristics, faults, lineaments, and seismic events allows detecting warning signs, including small displacements of parts of the slope, tension cracking, and reactivation of spring lines [ 3 , 4 , 5 , 6 ]. Furthermore, soil geomechanical properties, such as water content, porosity, grain sizes, plasticity index, methylene blue value (MBV), soil angle of internal friction, and cohesion, can play a significant role when trying to understand and predict slope soil failure mechanisms [ 3 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrical resistivity of the materials is a criterion showing a wide range of values, which is sensitive to several factors such physical properties of the materials (soil type, porosity, permeability etc. ), volume and conductivity of the water, and weathering and fracturing of the bedrock (Telford etal.,1990;Jongmans and Garambois, 2007;Ponzianietal.,2011;Epada et al, 2012). The geophysical method such as ERT can provide 2D or 3D models of the subsurface layers of the materials in the landslide for studying the slope (Suzuki and Higashi 2001;Lapenna et al, 2003Lapenna et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%